Advanced Thyroid Follicular Carcinoma in a Pregnant Woman - Victor Rocha Pinheiro; Bruno Minoru Miamoto; Júlia Thalita Queiróz Rocha; Carlos Segundo Paiva Soares; José Vicente Tagliarini; Roberto Antônio de Araujo Costa; Glaucia Maria F. da Silva Mazeto; Mariangela Esther Alencar Marques; Cristiano Claudino Oliveira (Hindawi Limited, 2019)
The diagnostic and therapeutic approach for pregnant women with thyroid nodules can present a challenge, especially concerning surgical procedures. In the context of malignant diagnosis, by fine needle aspiration (FNA), during pregnancy, the uncertainty lies in performing surgery. This article reports the case of a 41-year-old pregnant woman in her first gestation, who sought medical care complaining of right shoulder pain. Imaging workup depicted the destruction of the humeral head and involvement of the surrounding soft tissue. She was 20 weeks pregnant. The histological report favored the diagnosis of malignancy and the thyroid as the primary site. At 30 weeks of gestation, the patient underwent a cesarean section, a total thyroidectomy, and total resection of the metastasis. The child was born healthy, but one year after the diagnosis, the patient died. Bone and soft tissue metastasis of thyroid neoplasms are not very common and indicate poor prognosis.